Christianity among other religions andsecular world views in the quest for thecommon good in pluralistic societies - Nieder-Heitmann, Jan (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Amid a plurality of religions and secular world views, some of which claim to serve the common good while others restrict themselves to the private sphere – and yet others deny Christianity and other religions’s relevance in the public sphere – the church has to constantly reinterpret its own claims, as well as those of other religions and secular world views. The church has to do this in order to ascertain its relationship with other religions and world views, and their adherents in general, but more particularly with regard to specific public issues. Public theology needs to be intra-disciplinary with the theology of other religions, and in conversation with the science and philosophy of religion.